Legal Safeguards for Tourists as Consumers: An Analysis of Accident Incidences at Tourist Sites - Prima Anggriawan, Teddy; Kartika Wardhani, Shinfani (International Journal of Educational Research & Social Sciences, 2024)
Accidents at tourist sites significantly harm tourists who are also consumers. This study aims to investigate both preventive and repressive forms of legal protection for tourists, especially in cases of accidents at tourist destinations. The research employs a qualitative methodology with a normative research design, focusing on statutory regulations and legal concepts. The findings indicate that preventive legal protection is lacking due to inadequate implementation of consumer protection and tourism laws, resulting in incidents with casualties, such as the one at The Geong Limpakuwus Pine Forest Tourism in Sumbang, Banyumas. Repressive legal protection is also insufficient, as the accountability of tourist sites in providing insurance to victims has not been fulfilled. Consequently, the legal protection for tourists as consumers in accident scenarios is not effectively provided.